Indirubin alleviates CCl4-induced liver fibrosis by regulation of TGF-β-mediated signaling pathways - Xiaoying Li; Yuanzhi Yao; Lin Wei (Iranian Journal of Basic Medical Sciences, 2023)
Objective(s): Liver fibrosis is a common liver disease caused by chronic liver damage. However, there are currently no approved drugs available to treat it. Therefore, the therapeutic effect of indirubin on liver fibrosis was evaluated. This study investigated the protective effect and related molecular mechanism of indirubin against CCl4-induced liver fibrosis in mice.Materials and Methods: We first detected the effect of indirubin on liver fibrosis in mice (n=8 per group, 32 mice total) by ELISA, HE, and Masson staining. Subsequently, the proliferation of activated HSCs was detected by MTT and EdU. Finally, the changes of related proteins and signaling pathways in mice treated with indirubin were investigated by qRT-PCR and Western blot. One-way ANOVA or two-tailed student’s t-test was used for comparison between groups.Results: Firstly, we found that indirubin (25 mg/kg) therapy could attenuate liver injury and significantly down-regulate α-SMA (P=0.0038) and collagen 1 (P=0.0057) in the liver using CCl4-induced liver fibrosis in mice. Secondly, we showed that indirubin (25 μM) could significantly inhibit hepatic stellate cell (HSC) trans-differentiation into myofibroblasts and proliferation (P=0.0063) in HSC-T6 cells treated by TGF-β. Finally, we showed that indirubin could greatly reduce the protein levels of p-Smad2/3, p38, p-ERK, and p-JNK in vivo and in vitro.Conclusion: Our results suggested that indirubin alleviated liver fibrosis and HSC activation mainly through TGF-β-mediated signaling pathways in vivo and in vitro. In conclusion, our data showed that indirubin could be a promising clinical therapeutic drug for the prevention and treatment of liver fibrosis.